MORPHOLOGICAL CREATIVITY IN BRAND NAMING: WORD FORMATION AND DERIVATIONAL PROCESSES - Riska Safitri Siregar; Siti Aisyah; Rifandy Wijaya; Dimas Bagoes Prasetyo; Dewi Nurmala (PHILOLOGY Journal of English Language and Literature, 2026)
This research investigates the strategic intersection of morphological theory and commercial branding by examining the linguistic mechanisms behind 50 global consumer brands. The primary objective is to analyze the derivational processes and creative word-formation strategies that facilitate brand distinctiveness. Utilizing a mixed-method approach supported by a corpus-based analysis, this study evaluates the structural patterns and functional impact of various linguistic innovations. Drawing on frameworks of derivational morphology and advertising management, the findings reveal that non-standard linguistic strategies are pivotal for establishing market resonance. Statistical data from the processed corpus indicate that compounding is the most dominant process (44%), followed by coining/acronyms (26%) and blending (24%), while standard derivation remains minimal at 6%. The analysis demonstrates that brands frequently employ "language games" to optimize phonetic appeal and semantic density. This study concludes that morphological creativity is a vital instrument within the contemporary linguistic landscape, providing a unique "creative experience" that differentiates commercial entities in a competitive global market.